2009
DOI: 10.1111/j.1460-9592.2008.02861.x
|View full text |Cite
|
Sign up to set email alerts
|

Flexion compromises ventilation with the laryngeal tube suction II in children

Abstract: Although oropharyngeal sealing pressure is decreased with the head and neck extended, effective ventilation with LTS II can be performed like in the neutral position or the rotated position. While the sealing pressure is maintained with the head and neck flexed, flexion compromises the ventilation with LTS II in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…At flexion of 30° and more the majority of the delivered tidal volume could not reach the lungs owing to an extremely narrowed laryngeal inlet leading to a significant reduction in expired tidal volume to 7.6 ml·kg −1 at 30° flexion and 6 ml·kg −1 at 45° flexion from 9.1 ml·kg −1 in the neutral position. These results were in agreement with previous studies documenting loss of expired tidal volume at maximum neck flexion . In our previous report, we reported a decrease in expired tidal volume to 4.6 ml·kg −1 in maximum flexion of 45° from the neutral position.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…At flexion of 30° and more the majority of the delivered tidal volume could not reach the lungs owing to an extremely narrowed laryngeal inlet leading to a significant reduction in expired tidal volume to 7.6 ml·kg −1 at 30° flexion and 6 ml·kg −1 at 45° flexion from 9.1 ml·kg −1 in the neutral position. These results were in agreement with previous studies documenting loss of expired tidal volume at maximum neck flexion . In our previous report, we reported a decrease in expired tidal volume to 4.6 ml·kg −1 in maximum flexion of 45° from the neutral position.…”
Section: Discussionsupporting
confidence: 94%
“…Kim et al . demonstrated an increase in the PIP from 19 cm H 2 O in the neutral position to 32 cm H 2 O in maximum flexion with the Laryngeal Tube. In a similar study Biedler et al .…”
Section: Discussionmentioning
confidence: 92%
“…Bortone et al compared the laryngeal tube with a classic LMA in children and found that no laryngeal structures were identifiable in six of eleven children [39]. Kim et al demonstrated that the view of the laryngeal structures during the fibreoptic assessments of the LTS-II depended significantly on the position of the head [40]. Mihai et al were able to visualize the glottis only in 51% of the cases with the LTS-II [30].…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck movements alter the shape of the pharynx resulting in changes in the oropharangeal leak pressure (OPLP) and ventilation . Studies that have compared and quantified the OPLP and adequacy of ventilation with SADs in different head and neck positions have been done in the past, with differing results . Moreover, the majority of these studies have been done on an adult population .…”
Section: Introductionmentioning
confidence: 99%